Penerapan Digitalisasi UMKM Sebagai Upaya Peningkatan Kualitas Pemasaran Produk Di Keluarahan Medokan Ayu - Feri Ardiansyah; Dhani Ichsanuddin Nur (Jurnal Informasi Pengabdian Masyarakat, 2023)
The activity of implementing digitalization for SMEs as an effort to enhance the quality of product marketing in Medokan Ayu Ward is aimed at providing knowledge about digital marketing to the local community. The objective is to empower UMKM practitioners in Medokan Ayu Ward with further understanding of digital marketing strategies to strengthen their products. The methodology of this activity includes observation, obtaining permissions from partners, implementation, training, and evaluation. The implementation focuses on delivering materials on the importance of digital marketing for UMKM. The training results show that participants responded positively to the presented materials, with an average percentage of 85.4%. The activity was attended by all Micro, Small, and Medium Enterprises (UMKM) operating in Medokan Ayu Ward, who responded positively to the implementation of digitalization for the purpose of improving the quality of product marketing in the area.